Dasatinib sensitises KRAS-mutant cancer cells to mitogen-activated protein kinase kinase inhibitor via inhibition of TAZ activity. (August 2018) - Rao, Guanhua; Kim, In-kyu; Conforti, Fabio; Liu, Jing; Zhang, Yu-Wen; Giaccone, Giuseppe
Abstract: Purpose: Oncogenic KRAS mutations occur frequently in solid tumours, but no clinically applicable targeted strategy is yet available for treating human cancers with mutant KRAS . Here we aimed to identify a strategy for the treatment of KRAS-driven cancers. Experimental Design: Cell viability and colony forming assays were used to assess the in vitro effect of dasatinib and trametinib as single agents or in combination. Western blot was used to analyse the phosphorylated protein and total protein levels. Xenograft models were used to evaluate the in vivo effect of drug combination on KRAS-driven tumour growth. Results: Here, we report the discovery of a synergistic interaction between dasatinib (ABL and SRC family kinase inhibitor) and the mitogen-activated protein kinase kinase (MEK) inhibitor trametinib in KRAS -mutant cancer cells. We demonstrated that dasatinib enhanced the antitumour effect of trametinib against the KRAS -mutant cancer models both in vitro and in vivo, and the combination resulted in a significant reduction of cytoplasmic and nucleic TAZ protein level, and therefore decreased downstream protein levels of YAP/TAZ signalling pathway. Furthermore, direct knockdown of TAZ by small interfering RNA was able to increase the sensitivity of KRAS -mutant cells to trametinib treatment. Conclusion: These results indicate that dasatinib enhances the antitumour activity of MEK inhibitor through inhibition of TAZ activity and identify dasatinib and trametinib combination as a potential strategy for the treatment of KRAS-driven cancers. Highlights: Dasatinib has synergistic effect with trametinib for the treatment of KRAS-driven cancers. The drug combination decreases TAZ protein level in KRAS-mutant cancer cells. Knockdown of TAZ sensitises KRAS-mutant cells to trametinib treatment.